2017
DOI: 10.1186/s12877-017-0532-2
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of alcohol interactive medications and alcohol in older adults: a systematic review of prevalence and associated adverse outcomes

Abstract: BackgroundOlder adults are susceptible to adverse effects from the concurrent use of medications and alcohol. The aim of this study was to systematically review the prevalence of concurrent use of alcohol and alcohol-interactive (AI) medicines in older adults and associated adverse outcomes.MethodsA systematic search was performed using MEDLINE (PubMed), Embase, Scopus and Web of Science (January 1990 to June 2016), and hand searching references of retrieved articles. Observational studies reporting on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
0
37
1
2
Order By: Relevance
“…6 Medications that interact with alcohol are widely prescribed to people who drink alcohol. 7 Alcohol can also have a direct and adverse effect on many conditions for which medications are prescribed, even when consumption is lower than that which is defined as low risk in drinking guidelines. 3 The damaging effects of alcohol consumption on the health of older people in the UK are evident in higher alcohol related hospital admissions and mortality among people aged over 65 than in younger people.…”
Section: Health Risksmentioning
confidence: 99%
“…6 Medications that interact with alcohol are widely prescribed to people who drink alcohol. 7 Alcohol can also have a direct and adverse effect on many conditions for which medications are prescribed, even when consumption is lower than that which is defined as low risk in drinking guidelines. 3 The damaging effects of alcohol consumption on the health of older people in the UK are evident in higher alcohol related hospital admissions and mortality among people aged over 65 than in younger people.…”
Section: Health Risksmentioning
confidence: 99%
“…Lijekovi koji mogu biti potencijalni okidači neželjenih reakcija su najčešće: metronidazol, ketokonazol, tinidazol, trimetoprimsulfometoksazol, izosorbid dinitrat, nitroglicerin, pojedini preparati sulfonilureje. [12,13].…”
Section: Diskusijaunclassified
“…While a number of studies have investigated the concurrent use of alcohol and AI medicines among older adults, 9 there is still a lack of agreement regarding the inclusion of AI medicines across studies. Several studies have reported on a broad range of medication classes, using different drug reference sources and software to identify medications as AI, thus leading to a lack of consistency in the inclusion of these medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on a broad range of medication classes, using different drug reference sources and software to identify medications as AI, thus leading to a lack of consistency in the inclusion of these medicines. 9 Other studies focused on psychotropic medications alone. 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation